(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
A pressing problem of modern society is the impact of physical activity of elderly people in the context of their functional capabilities, which decrease with age. A person must constantly adapt to the conditions of functioning at all stages of his own life. With age and the natural decrease in the working capacity of individual organs and systems of the body, a person’s adaptive capabilities gradually deteriorate. However, today it is not fully understood to what extent the loss of these capabilities is an integral feature of aging, and to what extent it depends on changes in lifestyle, including physical activity. The assumption that the existing level of physical activity is extremely important for effective adaptation to different operating conditions seems to be quite reasonable. During the aging process, many pathophysiological changes occur in the human body that limit its functional capabilities. This period of human life is associated with a gradual decrease in physical working capacity, frequent cases of disability and concomitant chronic diseases. The purpose of the study is to theoretically and practically substantiate a comprehensive program using adaptive physical culture tools, which involves determining socio-psychological adaptation, psychological state and assessment of the quality of life of elderly women. Methods: theoretical analysis and generalization of data from scientific and methodological literature, pedagogical testing, questionnaires, methods of mathematical statistics. Elderly women need balanced physical activity to maintain health and creative longevity, taking into account their psychophysical characteristics and needs, aimed at stopping the processes of premature aging. The theoretical significance of the study lies in expanding and deepening knowledge about the content and methodology of physical culture and health-improving classes, the periods of classes with elderly women are characterized. The essence, goal, objectives and means of adaptive physical culture as factors of physical activity and improving the quality of life of women of this category are determined.